Successful diagnosis of Mycobacterium marinum infection by mNGS in a patient with Human Immunodeficiency Virus: a case report - Liu, Xinhua; Liu, Zengxin; Chen, Zhimin; Liu, Bo; Feng, Lizhi; Li, Linghua; Hong, Dengwei; Wang, Ru; He, Haolan (The Journal of Infection in Developing Countries, 2024)
Introduction: Mycobacterium marinum infection rarely occurs and has atypical symptoms. It is challenging to distinguish disseminated M. marinum infection from multifocal dermatosis caused by other factors clinically. Case Presentation: Herein, we reported a 68-year-old male patient with Human Immunodeficiency Virus (HIV) who presented redness and swelling in his left hand after being stabbed by marine fish for over 2 months. Mycobacterium tuberculosis infection was considered according to biochemical and pathological examinations, while empirical anti-infection treatment was ineffective. Result: The metagenomic next-generation sequencing (mNGS) detected a large amount of M. marinum sequences, and the patient was finally diagnosed with M. marinum infection. After one month of combination therapy with ethambutol, rifabutin, moxifloxacin, and linezolid, the swelling disappeared significantly. In this case, the successful application of mNGS in diagnosing and treating M. marinum infection has improved the understanding of the microbe both in the laboratory and clinically, especially in patients with HIV. Conclusions: For diseases with atypical symptoms or difficulty in determining the pathogens, mNGS is suggested in clinical procedures for rapid and accurate diagnosis and treatment.